Cracker culture : Celtic ways in the Old South - McWhiney, Grady (University of Alabama Press, 1988)
Cracker culture is a provocative study of social life in the Old South that probes the origin of cultural differences between the South and the North throughout American history. Fundamental differences between Southerners and Northerners shaped the course of antebellum America; their conflict in the 1860s was nto so much brother against brother as culture against culture.